Is percutaneous coronary intervention safe during uninterrupted direct oral anticoagulant therapy in patients with atrial fibrillation and acute coronary syndromes?. Issue 2 (14th July 2021) - De Luca, Leonardo; Rubboli, Andrea; Bolognese, Leonardo; Uguccioni, Massimo; Lucci, Donata; Blengino, Simonetta; Campodonico, Jeness; Meynet, Ilaria; Brach Prever, Silvia Maria; Di Lenarda, Andrea; Gabrielli, Domenico; Gulizia, Michele Massimo
Abstract : Objectives: No data on optimal management of patients with acute coronary syndromes (ACS) on long-term direct oral anticoagulants (DOACs) undergoing percutaneous coronary intervention (PCI) are available. Using the data of the Management of Antithrombotic TherApy in Patients with Chronic or DevelOping AtRial Fibrillation During Hospitalization for PCI study, we sought to compare the outcome of patients with ACS and atrial fibrillation (AF) who underwent PCI during uninterrupted DOAC (UDOAC group) and those who interrupted DOAC before PCI (IDOAC group). Methods: The primary outcomes of our analysis were the incidence of major adverse cardiovascular events (MACEs), a composite of death, cerebrovascular events, recurrent myocardial infarction or revascularisation and net adverse clinical events (NACEs), including major bleeding, at 6 months. Results: Among the 132 patients on long-term DOAC, 72 (54.6%) underwent PCI during UDOAC and 60 (45.4%) after IDOAC. The mean CHA2 DS2 -VASc score was 3.8±1.7 and 3.9±1.3 (p=0.89), while the HAS-BLED score was 2.5±1.0 and 2.5±0.9 (p=0.96), in UDOAC and IDOAC groups, respectively. The median time from hospital admission to PCI was 9.5 (IQR: 2.0–31.5) hours in UDOAC and 45.5 (IQR: 22-5–92.0) hours in IDOAC group (p<0.0001). A radial approach was used in 92%, and a drug-eluting stent was implanted in 98% of patients. At 6 months, the rates of MACE (13.9% vs 16.7%) and NACE (20.8% vs 21.7%) did not differ between UDOAC and IDOAC groups. At multivariable analysis, increasing CHA2 DS2 -VASc score (HR: 1.39; 95% CIs 1.05 to 1.83; p=0.02) resulted as the only independent predictor of NACE. Conclusions: Our study shows that PCI is a safe procedure during UDOAC in patients with concomitant ACS and AF.